The Integration Of Islamic Values In Learning to Conserve Natural Resource: An Effort to Strengthen Students Ecological Awareness - Farhana, Nida; Dewi Prameswari, Meutia; Amirullah, Amirullah (AL-WIJDÃN Journal of Islamic Education Studies, 2022)
This study aims to analyze the integration of Islamic values in fostering ecological awareness in the content of the material presented in the book theme 9 "Kayanya Negeriku" for fourth-grade elementary school. This research approach uses a qualitative literature study. The content of the material analyzed is the preservation of Indonesia's natural resources. The research results almost all of the material can be related to Islamic values or those contained in the Qur'an. The material is delivered in the form of contextual stories that bring students to think logically about facts and phenomena of everyday life. The conclusion of this research is the application of Islamic values in the attitude of growing a sense of love for the environment is very important, especially instilled in elementary school students in the preservation of natural resources. So that students have gratitude and are wise in utilizing nature by Allah's commands in the Qur'an so that it is not just knowledge that is implanted.   Keywords: Integration of Islamic Values, conservation of Natural Resources, Ecological Awareness